Traceability of database operations to mitigate risks in audit processes - Mayta Avalos, Cesar Augusto (2022)
In the field of databases, the lack of traceability of transactions or operations in a database is vital to respond to incidents that may originate within them, such as the alteration of unauthorized information. This article proposes an auditing model to mitigate risk using Oracle's object and transaction auditing approach. Finally, a laboratory was implemented in which the proposed model was deployed, ensuring the information's confidentiality, integrity, and availability.